Oxalic acid-free low-corrosion ITO etching liquid composition for flexible OLED and preparation method thereof

CN122978968APending Publication Date: 2026-10-27JIANGYIN RUNMA ELECTRONICS MATERIAL
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611085543.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-21
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0005]本发明的目的在于提供一种无草酸型低腐蚀柔性OLED用ITO蚀刻液组合物及其制备方法,以解决现有ITO蚀刻液在柔性基板应用中需高温操作导致PI基板热损伤、草酸结晶析出、金属离子再沉积及润湿性不足的技术问题

Benefits of technology

现有技术中强酸体系需在45℃以上高温操作导致PI严重黄变(ΔYI>7),草酸体系易结晶析出且金属残留缺陷密度高达20个/cm2以上,常规表面活性剂体系接触角>50°导致润湿不足,均无法同时兼顾低温保护、溶液稳定与均匀蚀刻的综合要求。本发明中通过N-乙基硫脲、电解质分散剂和烷基糖苷配合作用,在低温条件下(30℃)即可实现高效ITO蚀刻,同时降低PI基板黄变指数,解决了蚀刻液絮凝沉淀和金属离子再沉积问题,同时能够降低蚀刻液组合与PI接触角降,显著改善润湿均匀性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application belongs to the technical field of etching solution, and particularly relates to an oxalic acid-free low-corrosion ITO etching solution composition for flexible OLED and a preparation method thereof. The ITO etching solution composition comprises, in percentage by mass, 35-75% of mixed acid, 0.5-3% of N-ethyl thiourea, 0.3-5% of electrolyte dispersant, 0.05-0.8% of glycoside non-ionic surfactant, and the balance of water; wherein the mixed acid comprises a combination of hydrochloric acid, nitric acid and glacial acetic acid. The ITO etching solution composition can realize the effects of low-temperature efficient etching, PI substrate protection, solution stability and uniform etching.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of etching solution technology, and more specifically, relates to an oxalic acid-free, low-corrosion ITO etching solution composition for flexible OLEDs and its preparation method. Background Technology

[0002] Indium tin oxide (ITO) thin films are widely used as transparent conductive electrode materials in OLED display panels, touch panels, and flexible electronic devices. ITO thin film etching is a key process in the manufacturing of flexible display panels. Traditional etching solutions mostly use strong acids (such as HCl / HNO3) or oxalic acid systems, but there are two major bottlenecks: First, the rigid substrate has poor compatibility, and high-temperature (>45℃) etching causes deformation of the polyimide (PI) substrate; Second, the etching uniformity is low, and the etching rate difference in the curvature area of ​​the flexible panel is >30%. The existing process still has the following defects: (1) substrate damage risk, strong acid high-temperature etching causes yellowing and embrittlement of the PI substrate (industry standard IPC-9203); (2) severe side etching, the side etching ratio (ΔW) of conventional formulations is >0.5μm, which leads to short circuits; (3) high metal residue, In 3+ / Sn 4+ Ion redeposition forms micro-short circuit points (defect density > 20 / cm²). 2 (4) The process is difficult to control, and the etching endpoint fluctuation is >15%, which affects the line width accuracy.

[0003] To overcome the above bottlenecks, the industry has proposed a variety of ITO etching solution improvement schemes, mainly focusing on the optimization of etching agents, the development of corrosion inhibitors, and the compounding of additives. For example: (1) In terms of the optimization of etching agents, existing processes mostly use acidic aqueous solutions containing hydrochloric acid as etching solution compositions. Since hydrochloric acid system is inexpensive and has a good etching speed, it is widely used in forming copper wiring patterns and ITO transparent electrode patterns. CN108352318A discloses an etching solution composition for etching copper-based film, which is formed by an aqueous solution containing the following components: (A) at least one oxidant selected from trivalent iron ions and divalent copper ions at 0.1 to 30% by mass; (B) hydrogen chloride at 0.1 to 20% by mass; and (C) 1,3-dihydroxybenzene at 0.01 to 25% by mass. The patent claims that its etching solution composition has high stability, is difficult to generate precipitates, and can form wiring patterns with the desired dimensional accuracy. However, this technology is mainly for etching films containing copper-based layers. Its core lies in using 1,3-dihydroxybenzene to improve the stability of the etching solution, but it does not address the issue of low-temperature etching protection for flexible PI substrates. More importantly, the system contains a high concentration of ferric ions or divalent copper ions as oxidants. These metal ions may introduce additional metal contamination risks during the etching process, and the residues on the PI substrate surface are difficult to completely remove. In addition, the etching solution also needs to be operated at a high temperature to maintain the etching rate, failing to solve the problem of thermal damage to the PI substrate; (2) In terms of multilayer film etching, with the development of OLED display technology, multilayer electrode structures formed by ITO and metals such as Ag and Cu are becoming increasingly popular, which places higher demands on the selective etching capability of the etching solution. In the existing process, the etching of ITO-Ag-ITO multilayer films usually adopts a two-step method. The first step uses a phosphoric acid-nitric acid-acetic acid system to etch the upper ITO and Ag layers, and the second step uses a mixed acid solution of sulfuric acid and nitric acid or oxalic acid solution to etch the lower ITO layer. This two-step process is complex and inefficient, and the switching between different etching solutions can easily introduce cross-contamination.

[0004] In summary, existing ITO etching solutions have not yet been able to simultaneously address the challenges of low-temperature etching, PI substrate protection, and metal ion blocking. Therefore, developing an oxalic acid-free, low-corrosion etching solution composition that can efficiently etch ITO at low temperatures while protecting the integrity of the PI substrate and inhibiting metal ion redeposition has significant industrial value and broad application prospects. Summary of the Invention

[0005] The purpose of this invention is to provide an oxalic acid-free, low-corrosion ITO etching solution composition for flexible OLEDs and its preparation method, so as to solve the technical problems of existing ITO etching solutions requiring high-temperature operation in flexible substrate applications, which leads to thermal damage to the PI substrate, oxalic acid crystallization, metal ion redeposition, and insufficient wettability.

[0006] To achieve the objectives of this invention, the first aspect of this invention provides an oxalic acid-free, low-corrosion ITO etching solution composition for flexible OLEDs, comprising, by mass percentage: 35%–75% mixed acid, 0.5%–3% N-ethylthiourea, 0.3%–5% electrolyte dispersant, 0.05%–0.8% glycoside nonionic surfactant, with the balance being water.

[0007] In a preferred embodiment, the ITO etching solution composition comprises, by mass percentage: 51%–69% mixed acid, 0.8%–2% N-ethylthiourea, 0.35%–1% electrolyte dispersant, 0.1%–0.2% glycoside nonionic surfactant, and the balance being water.

[0008] Mixed acid A mixed acid refers to an etching agent composed of at least two acids. In one embodiment, the mixed acid includes a combination of hydrochloric acid, nitric acid, and glacial acetic acid.

[0009] In a preferred embodiment, the mass ratio of hydrochloric acid, nitric acid and glacial acetic acid is (25-35):(8-12):(18-22).

[0010] In this invention, hydrochloric acid refers to commercially available aqueous solution of hydrogen chloride (HCl), the mass content of which (i.e., the percentage of HCl gas in the total mass of hydrochloric acid solution) is generally 36% to 38%, for example 37%.

[0011] In this invention, nitric acid refers to commercially available aqueous nitric acid (HNO3) solution, with a mass content generally of 68% to 70%, for example, 68%.

[0012] The glacial acetic acid in this invention can be commercially available glacial acetic acid (CH3COOH) with a purity ≥99.5%, for example, 99.5%.

[0013] N-Ethiourea The N-ethylthiourea in this invention is commercially available and has a purity of ≥98%.

[0014] In this invention, N-ethylthiourea enables the ITO etching solution composition to maintain high etching activity at low temperatures of 5–35°C, while simultaneously increasing the ITO:PI etching selectivity ratio to over 50:1, significantly suppressing yellowing and thermal deformation of the PI substrate. This is likely because the thiourea group in the N-ethylthiourea molecule possesses multiple hydrogen bond donor / acceptor sites, which can form a strong hydrogen bond network with water molecules and glacial acetic acid, effectively disrupting the ordered arrangement of ice crystals and improving the low-temperature fluidity of the ITO etching solution composition, allowing it to maintain a homogeneous and stable state within the 5–35°C range. Simultaneously, the sulfur and amino nitrogen atoms in the N-ethylthiourea molecule possess lone pairs of electrons, which can specifically adsorb onto the PI substrate surface through coordination and van der Waals forces to form an adsorption layer. This adsorption layer preferentially covers the amide bond active sites on the PI surface, forming a dense molecular-level protective film that prevents H... + Cl - Etching active species penetrate and attack the PI substrate.

[0015] Electrolyte dispersant The electrolyte dispersant in this invention refers to a water-soluble electrolyte containing anionic groups (carboxylate and / or sulfonate groups). Its molecular chain has strong anionic functional groups such as carboxylate and / or sulfonate groups distributed on it. It can ionize in water to form negatively charged polymeric ions with high negative charge density and multi-site coordination ability. In one embodiment, the electrolyte dispersant includes at least one of sodium polyacrylate, sodium pyrophosphate, trisodium phosphate, tetrasodium phosphate, sodium hexametaphosphate, sodium polystyrene sulfonate, carboxymethyl cellulose, hydroxyethyl cellulose, and 2-acrylamido-2-methylpropanesulfonic acid.

[0016] In a preferred embodiment, the electrolyte dispersant comprises sodium polyacrylate, sodium polystyrene sulfonate, and 2-acrylamido-2-methylpropanesulfonic acid.

[0017] In a preferred embodiment, the mass ratio of sodium polyacrylate, sodium polystyrene sulfonate, and 2-acrylamido-2-methylpropanesulfonic acid is (2-5):(0.5-2.5):1, for example, 3.75:1.875:1, 4.17:2.08:1, or 4:2:1.

[0018] In this invention, it was discovered that the thiourea group in the N-ethylthiourea molecule reacts with dissolved In during the etching process. 3+ / Sn 4+Ions undergo strong coordination complexation reactions, forming insoluble thiourea-metal complex precipitates, leading to etching solution flocculation, substrate surface particle contamination, and consumption of effective components. In this invention, an electrolyte dispersant composition formed by compounding sodium polyacrylate, sodium polystyrene sulfonate, and 2-acrylamido-2-methylpropanesulfonic acid in a specific mass ratio, through the synergistic dispersion-complexation effect of anionic polymer chains, can disperse the flocculated precipitate of N-ethylthiourea-metal complex into stable nano-sized colloidal particles, while simultaneously inhibiting the formation of In... 3+ / Sn 4+ Achieving efficient complexation and sealing, the etching solution remains homogeneous and free of precipitation even after 48 hours of settling, reducing the density of residual metal defects to ≤1.2 defects / cm³. 2 It is speculated that this is because N-ethylthiourea reacts with In... 3+ / Sn 4+ The formed thiourea-metal coordination polymer flocs have locally positively charged surfaces, which provides an electrostatic driving force for the adsorption of anionic polymeric electrolytes. Specifically, carboxylate anions (-COO-) are densely distributed on the sodium polyacrylate molecular chains. - This compound can strongly adsorb onto the surface of flocculant particles. Its long polymer chains form a three-dimensional barrier layer around the particles, while simultaneously imparting a high-density negative charge to the particle surface. Through this dual repulsion, it deagglomerates micron-sized flocculent aggregates into stable colloidal particles <100nm. Furthermore, the sulfonate anion (-SO3-) in the sodium polystyrene sulfonate molecule... - ) for In 3+ It has strong coordination ability and can form stable In-sulfonate complexes, effectively locking free indium ions in solution; the amide group (-CONH-) and sulfonic acid group (-SO3H) in the 2-acrylamido-2-methylpropanesulfonic acid molecule synergistically complex Sn. 4+ This forms a stable five-membered ring chelate structure, blocking free tin ions and thus better stabilizing the reaction system.

[0019] The sodium polyacrylate in this invention is a water-soluble polymer compound obtained by polymerizing acrylic acid monomers and then neutralizing them with sodium hydroxide. In a preferred embodiment, the number average molecular weight of the sodium polyacrylate is 2000 to 8000, for example, 2000, 3000, 4000, 5000, 6000, 7000 or 8000.

[0020] The sodium polystyrene sulfonate in this invention is a water-soluble polymer electrolyte obtained by polymerization of sodium styrene sulfonate monomers. In a preferred embodiment, the number average molecular weight of the sodium polystyrene sulfonate is 10,000 to 30,000, for example, 10,000, 12,000, 15,000, 18,000, 20,000, 22,000, 25,000 or 30,000.

[0021] Glycoside nonionic surfactants Glycoside nonionic surfactants refer to alkyl glycosides, which are nonionic surfactants synthesized from natural renewable resources (glucose from starch hydrolysis and fatty alcohols derived from vegetable oils). In a preferred embodiment, the glycoside nonionic surfactant has an alkyl chain with 8 to 16 carbon atoms and a degree of polymerization of 1 to 3. For example, it can be a commercially available brand of glycoside nonionic surfactant APG0810, which has an alkyl chain with 8 to 10 carbon atoms and a degree of polymerization of about 1.0 to 1.5.

[0022] When electrolyte dispersants ionize in solution, they form a large number of hydrated ions, which significantly increases the bulk surface tension of the etching solution composition. This leads to poor spreadability of the etching solution composition on the PI substrate surface, specifically manifested as increased contact angle and more pinhole defects caused by bubble adhesion. In this invention, alkyl glycosides form an intermolecular hydrogen bond network with the carboxylate / sulfonate groups of the electrolyte dispersant through multiple hydroxyl groups in their molecules, synergistically reducing the surface tension of the etching solution composition and decreasing the contact angle of the PI substrate to below 20°.

[0023] water There are no special restrictions on the water used in this invention, but deionized water is preferred.

[0024] The second aspect of the present invention provides a method for preparing an oxalic acid-free, low-corrosion ITO etching solution composition for flexible OLEDs. The preparation method includes mixing a mixed acid, N-ethylthiourea, an electrolyte dispersant, a glycoside nonionic surfactant, and water to obtain the oxalic acid-free, low-corrosion ITO etching solution composition for flexible OLEDs.

[0025] In a preferred embodiment, the mixing is carried out in the following order: water is added to the reaction vessel first, then the mixed acid is added, then N-ethylthiourea is added, followed by the electrolyte dispersant, and finally the glycoside nonionic surfactant is added.

[0026] In a preferred embodiment, the mixed acid comprises hydrochloric acid, nitric acid, and glacial acetic acid, and the mixed acid is added in the following order: first nitric acid, then hydrochloric acid or glacial acetic acid. As an example, the mixed acid is added in the following order: first nitric acid, then hydrochloric acid, and finally glacial acetic acid; as another example, the mixed acid is added in the following order: first nitric acid, then glacial acetic acid, and finally hydrochloric acid. The system temperature is controlled to not exceed 40°C during the addition of nitric acid.

[0027] As an example, a method for preparing an ITO etching solution composition for oxalic acid-free, low-corrosion flexible OLEDs includes: (1) Add 60-80% of the formula amount of water to the reactor and start stirring; (2) Add nitric acid and stir for 3 to 8 minutes, keeping the temperature below 40°C; (3) Add hydrochloric acid and stir for 5 to 15 minutes; then add glacial acetic acid and continue stirring for 5 to 15 minutes; (4) Add N-ethylthiourea and stir for 10-20 minutes until completely dissolved; (5) Add electrolyte dispersant and stir for 15-25 minutes until completely dissolved; (6) Add glycoside nonionic surfactant and stir for 10-20 minutes; (7) Add the remaining water to adjust, stir for 5 to 15 minutes, and it is ready.

[0028] The preferred step (7) is followed by: (8) letting it stand for 20 to 40 minutes, then circulating it through a 0.2 to 0.45 μm filter to obtain an oxalic acid-free, low-corrosion flexible OLED ITO etching solution composition.

[0029] More preferably, the filter element is a PTFE (polytetrafluoroethylene) filter element.

[0030] Compared with the prior art, the present invention has at least the following technical effects: In existing technologies, strong acid systems require high-temperature operation above 45°C, leading to severe yellowing of PI (ΔYI > 7). Oxalic acid systems are prone to crystallization and precipitation, and the density of metal residue defects is as high as 20 per cm³. 2 The conventional surfactant system, with a contact angle >50°, results in insufficient wetting and cannot simultaneously meet the comprehensive requirements of low-temperature protection, solution stability, and uniform etching. This invention, through the combined action of N-ethylthiourea, an electrolyte dispersant, and an alkyl glycoside, achieves efficient ITO etching at low temperatures (30°C), while simultaneously reducing the yellowing index of the PI substrate. This solves the problems of flocculation and precipitation in the etching solution and metal ion redeposition, and also reduces the contact angle drop between the etching solution and the PI substrate, significantly improving wetting uniformity. Detailed Implementation

[0031] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0032] Example 1 I. Preparation of the components of the ITO etching solution composition: Weigh each component according to the following mass percentages: Hydrochloric acid (37% by mass, electronic grade): 30%; Nitric acid (68% by mass, electronic grade): 10%; Glacial acetic acid (purity ≥99.5%, electronic grade): 20%; N-Ethiourea (purity ≥98%): 1.2%; Sodium polyacrylate (number average molecular weight 4000): 0.3%; Sodium polystyrene sulfonate (number average molecular weight 20,000): 0.15%; 2-Acrylamido-2-methylpropanesulfonic acid (purity ≥99%): 0.08%; Alkyl glycoside (brand name APG0810, alkyl chain carbon number 8-10, degree of polymerization approximately 1.0-1.5): 0.15%; Deionized water: Replenish to 100%.

[0033] II. Preparation of ITO Etching Solution Composition At room temperature, add the ingredients in the following order: (1) Add 70% of the formula amount of deionized water to the reactor, turn on the stirrer, and set the speed to 400 rpm; (2) Add nitric acid slowly while stirring, and stir for 5 minutes until the mixture is uniform, while controlling the temperature not to exceed 40℃; (3) Slowly add hydrochloric acid and stir for 10 minutes; then slowly add glacial acetic acid and continue stirring for 10 minutes until well mixed; (4) Add N-ethylthiourea and stir for 15 minutes until completely dissolved; (5) Add sodium polyacrylate, sodium polystyrene sulfonate and 2-acrylamido-2-methylpropanesulfonic acid in sequence, and stir for 20 minutes until completely dissolved; (6) Add alkyl glycosides and continue stirring for 15 minutes; (7) Add the remaining deionized water to adjust, and continue stirring for 10 minutes; (8) After standing for 30 minutes, the solution is filtered through a 0.2μm PTFE (polytetrafluoroethylene) filter to obtain the ITO etching solution composition.

[0034] Example 2 I. Preparation of the components of the ITO etching solution composition: Weigh each component according to the following mass percentages: Hydrochloric acid (37% by mass, electronic grade): 25%; Nitric acid (68% by mass, electronic grade): 8%; Glacial acetic acid (purity ≥99.5%, electronic grade): 18%; N-Ethiourea (purity ≥98%): 2%; Sodium polyacrylate (number average molecular weight 3000): 0.5%; Sodium polystyrene sulfonate (number average molecular weight 15000): 0.25%; 2-Acrylamido-2-methylpropanesulfonic acid (purity ≥99%): 0.12%; Alkyl glycoside (brand name APG0810): 0.2%; Deionized water: Replenish to 100%.

[0035] II. Preparation of ITO Etching Solution Composition Same as Example 1.

[0036] Example 3 I. Preparation of the components of the ITO etching solution composition: Weigh each component according to the following mass percentages: Hydrochloric acid (37% by mass, electronic grade): 35%; Nitric acid (68% by mass, electronic grade): 12%; Glacial acetic acid (purity ≥99.5%, electronic grade): 22%; N-Ethiourea (purity ≥98%): 0.8%; Sodium polyacrylate (number average molecular weight 6000): 0.2%; Sodium polystyrene sulfonate (number average molecular weight 25,000): 0.1%; 2-Acrylamido-2-methylpropanesulfonic acid (purity ≥99%): 0.05%; Alkyl glycoside (brand name APG0810): 0.1%; Deionized water: Replenish to 100%.

[0037] II. Preparation of ITO Etching Solution Composition Same as Example 1.

[0038] Comparative Example 1 The method of Example 1 is followed, except that N-ethylthiourea is replaced with 1,3-dihydroxybenzene.

[0039] Comparative Example 2 The method is the same as in Example 1, except that N-ethylthiourea is replaced with potassium hydrogen sulfate.

[0040] Comparative Example 3 I. Preparation of the components of the ITO etching solution composition: Weigh each component according to the following mass percentages: Hydrochloric acid (37% by mass, electronic grade): 30%; Nitric acid (68% by mass, electronic grade): 10%; Glacial acetic acid (purity ≥99.5%, electronic grade): 20%; N-Ethiourea (purity ≥98%): 1.2%; Sodium polyacrylate (number average molecular weight 4000): 0.08%; Sodium polystyrene sulfonate (number average molecular weight 20,000): 0.15%; 2-Acrylamido-2-methylpropanesulfonic acid (purity ≥99%): 0.3%; Alkyl glycoside (brand name APG0810): 0.15%; Deionized water: Replenish to 100%.

[0041] II. Preparation of ITO Etching Solution Composition Same as Example 1.

[0042] Comparative Example 4 I. Preparation of the components of the ITO etching solution composition: Weigh each component according to the following mass percentages: Hydrochloric acid (37% by mass, electronic grade): 30%; Nitric acid (68% by mass, electronic grade): 10%; Glacial acetic acid (purity ≥99.5%, electronic grade): 20%; N-Ethiourea (purity ≥98%): 1.2%; Sodium polyacrylate (number average molecular weight 4000): 0.2%; Sodium polystyrene sulfonate (number average molecular weight 20,000): 3%; 2-Acrylamido-2-methylpropanesulfonic acid (purity ≥99%): 0.03%; Alkyl glycoside (brand name APG0810): 0.15%; Deionized water: Replenish to 100%.

[0043] II. Preparation of ITO Etching Solution Composition Same as Example 1.

[0044] Comparative Example 5 I. Preparation of the components of the ITO etching solution composition: Weigh each component according to the following mass percentages: Hydrochloric acid (37% by mass, electronic grade): 30%; Nitric acid (68% by mass, electronic grade): 10%; Glacial acetic acid (purity ≥99.5%, electronic grade): 20%; N-Ethiourea (purity ≥98%): 1.2%; Polyetheramine (brand name D230); 0.53%; Alkyl glycoside (brand name APG0810): 0.15%; Deionized water: Replenish to 100%.

[0045] II. Preparation of ITO Etching Solution Composition At room temperature, add the ingredients in the following order: (1) Add 70% of the formula amount of deionized water to the reactor, turn on the stirrer, and set the speed to 400 rpm; (2) Add nitric acid slowly while stirring, and stir for 5 minutes until the mixture is uniform. Control the temperature of the reactor to not exceed 40°C. (3) Slowly add hydrochloric acid and stir for 10 minutes; then slowly add glacial acetic acid and continue stirring for 10 minutes until well mixed; (4) Add N-ethylthiourea and stir for 15 minutes until completely dissolved; (5) Add polyetheramine and stir for 20 minutes until completely dissolved; (6) Add alkyl glycosides and continue stirring for 15 minutes; (7) Add the remaining deionized water to adjust, and continue stirring for 10 minutes; (8) After standing for 30 minutes, the solution is filtered through a 0.2μm PTFE (polytetrafluoroethylene) filter to obtain the ITO etching solution composition.

[0046] Comparative Example 6 I. Preparation of the components of the ITO etching solution composition: Weigh each component according to the following mass percentages: Hydrochloric acid (37% by mass, electronic grade): 40%; Nitric acid (68% by mass, electronic grade): 20%; N-Ethiourea (purity ≥98%): 1.2%; Sodium polyacrylate (number average molecular weight 4000): 0.3%; Sodium polystyrene sulfonate (number average molecular weight 20,000): 0.15%; 2-Acrylamido-2-methylpropanesulfonic acid (purity ≥99%): 0.08%; Alkyl glycoside (brand name APG0810): 0.15%; Deionized water: Replenish to 100%.

[0047] II. Preparation of ITO Etching Solution Composition At room temperature, add the ingredients in the following order: (1) Add 70% of the formula amount of deionized water to the reactor, turn on the stirrer, and set the speed to 400 rpm; (2) Slowly add nitric acid and stir for 10 minutes, controlling the temperature not to exceed 40°C; then slowly add hydrochloric acid and continue stirring for 10 minutes until the mixture is homogeneous; (3) Add N-ethylthiourea and stir for 15 minutes until completely dissolved; (4) Add sodium polyacrylate, sodium polystyrene sulfonate and 2-acrylamido-2-methylpropanesulfonic acid in sequence, and stir for 20 minutes until completely dissolved; (5) Add alkyl glycosides and continue stirring for 15 minutes; (6) Add the remaining deionized water to adjust, and continue stirring for 10 minutes; (7) After standing for 30 minutes, the solution is filtered through a 0.2μm PTFE (polytetrafluoroethylene) filter to obtain the ITO etching solution composition.

[0048] Comparative Example 7 The method according to Example 1 differs in that, Replace hydrochloric acid with tartaric acid and glacial acetic acid with potassium bisulfate.

[0049] Comparative Example 8 The method according to Example 1 differs in that, Replace glacial acetic acid with oxalic acid.

[0050] Comparative Example 9 The method according to Example 1 differs in that, Replace the alkyl glycoside with polyethylene glycol 400.

[0051] Performance testing: 1. Etching Rate Test: A PI flexible substrate (50 μm thick) coated with a 100 nm ITO thin film was placed in an ITO etching solution at 30 °C and etched using a spray etching method (spray pressure 0.2 MPa). The time required for complete etching of the ITO thin film was recorded, and the etching rate (nm / s) was calculated. Etching rate (nm / s) = ITO film thickness (100 nm) / complete etching time (s).

[0052] 2. Yellowing Index (ΔYI) Test of PI Substrate: Immerse the PI substrate in a 30℃ ITO etching solution for 180 seconds, rinse with deionized water for 60 seconds, and dry with nitrogen. Measure the yellowing index (YI) of the substrate before and after etching using a UV-Vis spectrophotometer (equipped with an integrating sphere accessory). Calculate the difference in yellowing index ΔYI according to ASTM E313 standard.

[0053] 3. Solution stability test: The ITO etching solution compositions of each example and comparative example were placed in colorless transparent glass bottles, sealed, and placed in a constant temperature chamber at 35°C for 48 hours. After standing for 48 hours, the bottom of the solution was observed visually (with the help of a strong flashlight) to see if any precipitate or flocculent material was produced.

[0054] 4. Metal ion redeposition defect density test: After etching, 10 fields of view (each field of view area 0.1 mm²) were randomly selected using a scanning electron microscope (SEM) at 1000x magnification. 2 ), in the statistical perspective, due to In 3+ / Sn 4+ The number of granular defects formed by redeposition is averaged and converted into defect density per unit area (defects / cm²). 2 ).

[0055] 5. Contact Angle Test: Using a contact angle meter, at 25°C, the ITO etching solution composition was dropped onto the surface of the PI substrate (droplet volume 2μL), and the static contact angle between the droplet and the PI substrate surface was measured using the seated drop method. Each sample was measured 5 times at different locations, and the average value was taken.

[0056] The performance test results are shown in Table 1.

[0057] Table 1 Performance Test Results As can be seen from the above performance test results, the ITO etching solution composition of the present invention can achieve the effects of low-temperature and high-efficiency etching, PI substrate protection, solution stability and uniform etching.

[0058] Furthermore, as can be seen from the above data, the etching rate and PI yellowing in Examples 1-3 are excellent. In Comparative Examples 1 and 2, replacing N-ethylthiourea with 1,3-dihydroxybenzene and potassium hydrogen sulfate resulted in a decrease in etching rate of about 40% to 47% and severe deterioration of PI yellowing. Although Comparative Example 6 (without glacial acetic acid) had a fast etching rate, the PI yellowing was extremely severe (ΔYI=12.5). This indicates that in this invention, the synergy between N-ethylthiourea and glacial acetic acid can better achieve the effect of low-temperature protection.

[0059] Examples 1-3 all showed no precipitation and had less than 1.5 metal residue defects per cm. 2 Comparative Example 5 (using polyetheramine instead of sodium polyacrylate, sodium polystyrene sulfonate, and 2-acrylamido-2-methylpropanesulfonic acid) produced a large amount of flocculent material and had high metal residue; Comparative Examples 3-4 (where the ratio of sodium polyacrylate, sodium polystyrene sulfonate, and 2-acrylamido-2-methylpropanesulfonic acid was not within the preferred range) all showed precipitation with metal residue ≥10 particles / cm³. 2This indicates that by using sodium polyacrylate, sodium polystyrene sulfonate, and 2-acrylamido-2-methylpropanesulfonic acid in a suitable mass ratio, the stability of the solution can be better achieved and the defects of metal residue can be reduced.

[0060] The PI contact angle of Example 1 was only 17°, while the contact angle of Comparative Example 9 (with PEG-400 replacing alkyl glycosides) was as high as 52°, indicating extremely poor wettability. This shows that alkyl glycosides in this invention can better improve the wettability of the ITO etching solution composition.

[0061] The above experimental results further demonstrate the importance of the technical solution defined in this invention to its technical effect.

[0062] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. An oxalic acid-free, low-corrosion ITO etching solution composition for flexible OLEDs, characterized in that, The mixture comprises, by mass percentage: 35%–75% mixed acid, 0.5%–3% N-ethylthiourea, 0.3%–5% electrolyte dispersant, 0.05%–0.8% glycoside nonionic surfactant, and the balance being water; wherein the mixed acid comprises a combination of hydrochloric acid, nitric acid, and glacial acetic acid.

2. The ITO etching solution composition according to claim 1, characterized in that, The ITO etching solution composition comprises, by mass percentage: 51%–69% mixed acid, 0.8%–2% N-ethylthiourea, 0.35%–1% electrolyte dispersant, 0.1%–0.2% glycoside nonionic surfactant, and the balance being water.

3. The ITO etching solution composition according to claim 1, characterized in that, The mass ratio of hydrochloric acid, nitric acid and glacial acetic acid is (25-35):(8-12):(18-22).

4. The ITO etching solution composition according to claim 1, characterized in that, The electrolyte dispersant includes at least one of sodium polyacrylate, sodium pyrophosphate, trisodium phosphate, tetrasodium phosphate, sodium hexametaphosphate, sodium polystyrene sulfonate, carboxymethyl cellulose, hydroxyethyl cellulose, and 2-acrylamido-2-methylpropanesulfonic acid.

5. The ITO etching solution composition according to claim 4, characterized in that, The electrolyte dispersant includes sodium polyacrylate, sodium polystyrene sulfonate, and 2-acrylamido-2-methylpropanesulfonic acid.

6. The ITO etching solution composition according to claim 5, characterized in that, The mass ratio of sodium polyacrylate, sodium polystyrene sulfonate, and 2-acrylamido-2-methylpropanesulfonic acid is (2-5):(0.5-2.5):

1.

7. The ITO etching solution composition according to claim 5 or 6, characterized in that, The number average molecular weight of the sodium polyacrylate is 2000-8000; the number average molecular weight of the sodium polystyrene sulfonate is 10000-30000.

8. The ITO etching solution composition according to claim 1, characterized in that, The glycoside nonionic surfactant has an alkyl chain with 8 to 16 carbon atoms and a degree of polymerization of 1 to 3.

9. A method for preparing an oxalic acid-free, low-corrosion flexible OLED ITO etching solution composition according to any one of claims 1 to 8, characterized in that, The preparation method includes mixing a mixed acid, N-ethylthiourea, an electrolyte dispersant, a glycoside nonionic surfactant, and water to obtain an oxalic acid-free, low-corrosion ITO etching solution composition for flexible OLEDs.

10. The preparation method according to claim 9, characterized in that, The mixing process involves adding the following ingredients in the following order: first, water is added to the reaction vessel, then the mixed acid is added, followed by N-ethylthiourea, then the electrolyte dispersant is added, and finally the glycoside nonionic surfactant is added.

Citation Information

Patent Citations

  • Etching fluid composition and etching method

    CN108352318A